¿por qué "el milagro del interés compuesto" lleva a las crisis financieras? (2009)
In this paper I want to discuss the financial sector’s tendency to dominate, deflate and polarize economies, thwarting economic potential. Understanding these financial dynamics is essential to explain why all nations are not operating up to the technological potential toward which classical liberalism aimed, and why the world economy is polarizing, as are domestic economies even in the most advanced industrial nations.